2022
DOI: 10.1186/s12864-022-08858-1
|View full text |Cite
|
Sign up to set email alerts
|

A heat shock 70kDa protein MaltHSP70-2 contributes to thermal resistance in Monochamus alternatus (Coleoptera: Cerambycidae): quantification, localization, and functional analysis

Abstract: Background Heat Shock Proteins 70 (HSP70s) in insects act on a diverse range of substrates to assist with overcoming extreme high temperatures. MaltHSP70-2, a member of HSP70s, has been characterized to involve in the thermotolerance of Monochamus alternatus in vitro, while quantification and localization of MaltHSP70-2 in various tissues and its functional analysis in vivo remain unclear. Results In this study, temporal expression of MaltHSP70-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…However, the molecular mechanisms underpinning this adaptive response remained to be elucidated. Our previous studies certi ed that the HSP20s contributed to the reproduction-related heat tolerance of M. alternatus (Li et al, 2022;Li et al, 2023). Building on these ndings, the present study aimed to identify the speci c substrate proteins interacting with MaltHSP20-5, which emerged as the most critical among these HSP20s, within the testes and ovaries.…”
Section: Reproductive Parameters Could Recover From Heat Stressmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the molecular mechanisms underpinning this adaptive response remained to be elucidated. Our previous studies certi ed that the HSP20s contributed to the reproduction-related heat tolerance of M. alternatus (Li et al, 2022;Li et al, 2023). Building on these ndings, the present study aimed to identify the speci c substrate proteins interacting with MaltHSP20-5, which emerged as the most critical among these HSP20s, within the testes and ovaries.…”
Section: Reproductive Parameters Could Recover From Heat Stressmentioning
confidence: 89%
“…The transcriptome data revealed that the gene number and up-regulation fold of HSPs are dominant after heat stress (Li et al, 2020). Subsequently, we found that six HSP70s and thirteen HSP20s were involved in the heat response of M. alternatus and possessed molecular high chaperone activity (Li et al, 2021;Li et al, 2022). More importantly, we innovatively discovered that one HSP20, MaltHSP20-5, accumulated in the ovary and testis and provide protection for reproductive processes under high temperature (Li et al, 2023).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Adults were maintained in a 14 h:10 h, light:dark photoperiod, whereas eggs, larvae and pupae were reared in continuous darkness (0 h:24 h, light:dark). All life stages were kept at a constant temperature of 25 ± 0.5 °C and 70 ± 5% relative humidity (RH), in line with the methods described by Li et al 25…”
Section: Experimental Insectsmentioning
confidence: 99%
“…The adults of M. alternatus used in this study were taken from a laboratory colony established from fourth-instar larvae collected from dead Pinus massoniana trees infested by B. xylophilus in Nanchang city, Jiangxi Province, China (28°50′45.6″N, 115°32′55.6″E) in Sep. 2020. The M. alternatus larvae, pupae, adults, and eggs were reared as previously described in a photoperiod of 14 hours light: 10 hours dark for adults and a photoperiod of 0 hour light:24 hours dark for eggs, larvae, and pupae at 25 ± 0.5°C with 70 ± 5% relative humidity (RH) (Li et al 2022).…”
Section: Insect Rearing and Collectionmentioning
confidence: 99%